After Tupac & D Foster - Woodson, Jacqueline (New York, N.Y. Puffin Books, 2010)
In the New York City borough of Queens in 1996, three girls bond over their shared love of Tupac Shakur's music, as together they try to make sense of the unpredictable world in which they live.
"First published in the United States of America by G.P. Putnam's Sons...2008"--T.p. verso.
A Newbery Honor Book
UCWS-2014-G-1638 donated by Prof. Eric Julian Manalastas
Keywords: Shakur, Tupac -- 1971-1996 -- Fiction; Coming of age -- Fiction; Friendship -- Fiction; African Americans -- Fiction; Queens (New York, N.Y.) -- Fiction